Closing the Window on Light Charged Higgs Bosons in the NMSSM - Johan Rathsman; Thomas Rössler (Advances in High Energy Physics)
In the Next-to-Minimal SuperSymmetric Model (NMSSM) the lightest CP-odd Higgs bosons (a1) can be very light. As a consequence, in addition to the standard charged Higgs boson (h±) decays considered in the MSSM for a light charged Higgs (mh±<mt), the branching fraction for h±→a1W can be dominant. We investigate how this signal can be searched for in tt- production at the Large Hadron Collider (LHC) in the case that (ma1≳2mB) with the a1 giving rise to a single bb--jet and discuss to what extent the LHC experiments are able to discover such a scenario with an integrated luminosity ~20 fb−1. We also discuss the implications of the possible Higgs-signal observed at the LHC.